EP205/#663 BRCA testing in Kazakhstani women with high-grade serous ovarian cancer. (4th December 2022) - Satanova, Alima; Kaidarova, Dilyara; Bolatbekova, Raikhan; Kukubassov, Yerlan; Madina, Orazgaliyeva; Ossikbayeva, Saniya; Kurmanova, Anar; Aydarov, Askar; Bertleuov, Orynbassar; Kaldybekov, Dauren
Abstract : Objectives: Up to 25–40% of cases high grade serous ovarian cancer (OC) associated with mutations in the BRCA genes. The knowledge of the BRCA mutation allows determining the prognosis of the disease and a personalized treatment using PARP inhibitors. More than 1, 000 new cases and 500 deaths from ovarian cancer are detected annually in Kazakhstan (KZ). The aim of this study was to examine the rate of BRCA1/2 in a retrospective cohort of kazakhstani women with high-grade serous ovarian carcinoma. Methods: GynOnc- genetic counselors initiated retrospective genetic testing was implemented at a KazIOR. DNA isolation from tumor tissue was performed using the cobas® DNA sample preparation kit (Roche Diagnostics, Basel, Switzerland). Genomic DNA was amplified using the AmpliSeq BRCA1 and BRCA2 panel. The DNA Libraries were pooled, barcoded, and sequenced. Data was analyzed using SPSS 23.0 and medians were reported Results: 42 patients diagnosed with SOC after January 2018 were included to genetic testing for a panel of ovarian cancer susceptibility genes. The prevalence of BRCA pathogenic variants was 45.2% (19/42). Study of history of OC women showed that the majority (78%) of patients with BRCA associated OC had sensitivity to platinum-based chemotherapy and 36.8% of cases had a hereditary burden of breast cancer or OC. Conclusions: BRCA1/2 mutations are common in women with high grade serous OC. All womendiagnosed with high grade serous OC should be considered to be candidates for genetic testing and in the result of this should be candidates to personalized treatment using PARP inhibitors .